Employment, innovation, and interfirm networks - Andrea Fabrizi; Giuseppe Garofalo; Giulio Guarini; Valentina Meliciani (PSL Quarterly Review, 2020)
This paper studies the employment impact of business network agreements, an innovative policy instrument introduced in Italy in 2010 to stimulate interfirm cooperation, with the aim of increasing innovative capacity and market competitiveness. We estimate the impact of these networks on employment for a panel of Italian firms using a system generalized method of moments and considering the literature on the employment impact of innovation. We find that networks, which can be interpreted as a form of open innovation, have a positive impact on employment; moreover, this impact appears positively influenced by sectoral and regional heterogeneity of firms and the region's innovation capacities. Overall, the results suggest that participation in networks where firms share industrial, commercial, and technical knowledge improves firm performance, creating synergies that help firms, especially small and medium-sized enterprises, to manage the growing complexity of knowledge and the fierce competition arising from increasingly globalized markets.
Keywords: D85; J2; O36; 330; interfirm networks; employment; innovation; GMM system